Diagnostic Imaging Performance of Acute Cholecystitis: A Ten Years Systematic Review - Laksono, Bella Sugih; Yazidah, Iklima Fauzi (The International Journal of Medical Science and Health Research, 2024)
Background: Acute cholecystitis is a common surgical emergency and ultrasound (US) is currently considered the first-line diagnostic imaging test. The relative accuracy of computed tomography (CT) in detecting acute cholecystitis has received little attention in the literature. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Ultrasound (US) is a good imaging modality for the diagnosis of acute cholecystitis with discriminative power.